2019
DOI: 10.21276/ijcmr.2019.6.12.34
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Transfusion Transmissible Infections among Blood Donors at a Tertiary Care Teaching Hospital in Central India

Abstract: Introduction: Blood transfusion is both a life saving measure in many medical and surgical emergencies and a source of transfusion transmitted infections. So a provision for strict criteria in recruitment and deferral of blood donors may improve safe transfusion practice. The present study was conducted to estimate the prevalence of transfusion transmitted infections in voluntary and replacement donors at a tertiary care teaching hospital in Indore,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Our study results shows, overall cumulative frequency of TTIs in blood donors was 2.038%, and frequency of HBV, HCV, HIV-I/II, VDRL and MP were 1.111%, 0.431%, 0.201%, 0.29% and 0.006% respectively. Present study result shows a higher Prevalence of TTIs than Tehran, Iran (0.515%)[ 21 ] and studies from India; Gujarat (0.77%)[22], Telangana (0.96%) [ 23 ], Ranchi (1.59%)[ 24 ], Odisha (1.89%) [ 25 ], central India(1.43%)[ 26 ] and Ahmedabad (0.58%) [ 27 ]. Compared to present study higher prevalence of TTIs reported from western region of Saudi Arabia (7.93%), Equatorial New Guinea (18.7%), Mozambique (37.39%) and Burkina Faso (24%)[ 20 ], Peshawar, Pakistan (5.33%)[ 28 ], WR Saudi Arabia(7.93%)[ 20 ], NW, Ethiopia (5.43%)[ 29 ], Eastern Ethiopia (7.06%)[ 30 ] and Brazil (Brazil%)[ 31 ].…”
Section: Discussionmentioning
confidence: 56%
“…Our study results shows, overall cumulative frequency of TTIs in blood donors was 2.038%, and frequency of HBV, HCV, HIV-I/II, VDRL and MP were 1.111%, 0.431%, 0.201%, 0.29% and 0.006% respectively. Present study result shows a higher Prevalence of TTIs than Tehran, Iran (0.515%)[ 21 ] and studies from India; Gujarat (0.77%)[22], Telangana (0.96%) [ 23 ], Ranchi (1.59%)[ 24 ], Odisha (1.89%) [ 25 ], central India(1.43%)[ 26 ] and Ahmedabad (0.58%) [ 27 ]. Compared to present study higher prevalence of TTIs reported from western region of Saudi Arabia (7.93%), Equatorial New Guinea (18.7%), Mozambique (37.39%) and Burkina Faso (24%)[ 20 ], Peshawar, Pakistan (5.33%)[ 28 ], WR Saudi Arabia(7.93%)[ 20 ], NW, Ethiopia (5.43%)[ 29 ], Eastern Ethiopia (7.06%)[ 30 ] and Brazil (Brazil%)[ 31 ].…”
Section: Discussionmentioning
confidence: 56%